Implementasi Hak Restitusi Korban Tindak Pidana Kekerasan Seksual - Muhammad Rifky Darmawan; Anselma Dyah Kartikahadi; Dominikus Rato; Fendi Setyawan (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Sexual violence in Indonesia is increasingly prevalent, both against men and women. Victims of sexual violence have the right to restitution that must be fulfilled by law enforcement officials. However, the implementation is still not optimal if you look at the decision 80/Pid.Sus/2023/PN Kik. Therefore, this research examines the fulfillment of restitution rights for victims of sexual violence from the perspective of legal protection theory. This research uses legal research methods using statutory, conceptual, and case approaches. Decision Number 80/Pid.Sus/2023/PN Kik still does not implement the fulfillment of restitution for victims of sexual violence, which should be the obligation of the judge to determine the amount of restitution that will later be given. This is not in line with the theory of legal protection put forward by Satjipto Rahardjo and Philpus M. Hadjon. The lack of awareness of law enforcement officials to fulfill victims of sexual violence requires the protection of witnesses and victims with the Witness and Victim Companion Program.